Probing Surface and Interfacial Tension of Ionic Liquids in Vacuum with the Pendant Drop and Sessile Drop Method - Paap, Ulrike; Kreß, Bernd; Steinrück, Hans-Peter; Maier, Florian (International Journal of Molecular Sciences, 2022)
We report on the surface and interface tension measurements of the two ionic liquids (ILs) [C8C1Im][PF6] and [m(PEGn)2Im]I (n = 2, 4, 6) in a surface science approach. The measurements were performed in a newly developed and unique experimental setup, which allows for surface tension (ST) measurements using the pendant drop method and for contact angle measurements using the sessile drop method under the well-defined conditions of a high vacuum (from 10−7 mbar). The setup also allows for in vacuum transfer to an ultrahigh vacuum system for surface preparation and analysis, such as in angle-resolved X-ray photoelectron spectroscopy. For [C8C1Im][PF6], we observe a linear decrease in the surface tension with increasing temperature. The ST measured under high vacuum is consistently found to be larger than under ambient conditions, which is attributed to the influence of water uptake in air by the IL. For [m(PEGn)2Im]I (n = 2, 4, 6), we observe a decrease in the ST with increasing polyethylene glycol chain length in a vacuum, similar to very recent observations under 1 bar Argon. This decrease is attributed to an increasing enrichment of the PEG chains at the surface. The ST data obtained under these ultraclean conditions are essential for a fundamental understanding of the relevant parameters determining ST on the microscopic level and can serve as a benchmark for theoretical calculations, such as molecular dynamic simulations. In addition to the ST measurements, proof-of-principle data are presented for sessile drop measurements in HV, and a detailed description and characterization of the new setup is provided.
CRIS-Team Scopus Importer:2022-11-25
Keywords: interface tension; ionic liquids (ILs); pendant drop; sessile drop; surface science; surface tension; vacuum